PPAR γ Prevents Neuropathic Pain by Down-Regulating CX3CR1 and Attenuating M1 Activation of Microglia in the Spinal Cord of Rats Using a Sciatic Chronic Constriction Injury Model - Li, Xilei; Guo, Qulian; Ye, Zhi; Wang, E.; Zou, Wangyuan; Sun, Zhihua; He, Zhenghua; Zhong, Tao; Weng, Yingqi; Pan, Yundan (Frontiers in Neuroscience, 2021)
Background: Previous studies have proved that peripheral nerve injury is involved in the pathogenesis of neuropathic pain (NP). The peripheral nerve injury primes spinal M1 microglia phenotype and produces pro-inflammatory cytokines, which are responsible for neurotoxic and neuronal hyper-excitable outcomes. Spinal peroxisome proliferator-activated receptor gamma (PPAR γ) has been shown to play an anti-inflammatory role in the development of NP. However, the role of PPAR γ in attenuating the pathological pathway of spinal microgliosis is still unknown. Methods: Sprague-Dawley rats (male, aged 8-10 weeks) were randomly divided into three groups, i.e., a control group, a neuropathic pain group, and a neuropathic pain + lentivirus encoding PPAR γ (LV-PPAR γ) group. The sciatic chronic constriction injury (CCI) model was used to induce NP in rats. Pain behavior was assessed by monitoring the rat hind-paw withdrawal threshold to mechanical stimuli and withdrawal latency to radiant heat. The LV-PPAR γ was intrathecally infused 1 day before CCI. Western blot analysis and real-time qPCR were used to detect the microglia phenotypic molecules and CX3CR1 expression in the spinal cord. In vitro, BV-2 microglia cells were transfected with LV-PPAR γ and incubated with lipopolysaccharides (LPS), and the levels of M1 microglia phenotypic molecules and CX3CR1 in BV-2 microglia cells were assessed by western blot analysis, real-time qPCR, and enzyme-linked immunosorbent assay. Results: Preoperative intrathecal infusion of LV-PPAR γ attenuated pain in rats 7 days post-CCI. The M1-microglia marker, CX3CR1, and pro-inflammatory signaling factors were increased in the spinal cord of CCI rats, while the preoperative intrathecal infusion of LV-PPAR γ attenuated these changes and increased the expression of IL-10. In vitro, the overexpression of PPAR γ in BV-2 cells reduced LPS-induced M1 microglia polarization and the levels of CX3CR1 and pro-inflammatory cytokines. Conclusion: Intrathecal infusion of LV-PPAR γ exerts a protective effect on the development of NP induced by CCI in rats. The overexpression of PPAR γ may produce both analgesic and anti-inflammatory effects due to inhibition of the M1 phenotype and CX3CR1 signaling pathway in spinal microglia.